Talent Management in The Digital Era: Utilizing Technology for Recruitment and Retention at PT Benawa (Advertising and Printing) Banjarbaru - Firdaus, Firdaus; Ambarwati, Riris; Mardah, Siti; Khuzaini, Khuzaini (International Journal of Economics (IJEC), 2025)
In the increasingly advanced digital era, companies in various sectors must adapt to technological changes to remain competitive. PT Benawa, an advertising and printing company in Banjarbaru, faces challenges in talent management amidst digital transformation. This study aims to explore how PT Benawa utilizes technology to improve the recruitment and retention process of talent. The use of information and communication technology, including AI-based recruitment software, HRIS, and data-based employee retention platforms, has increased the efficiency and effectiveness of the talent management process. This study uses the ADDIE model to ensure that the application of technology is carried out systematically and structured. The results of the study show that technology can improve employee experience, work flexibility, and company image, despite challenges in adapting to technology and changing organizational culture. With the right strategy, PT Benawa can achieve a competitive advantage in talent management in the digital era.